Productivity improvement through method study and line balancing analysis [electronic resource] - Muhammad Fadly Zainal Abidin, 1985-; Wan Harun Wan Hamid, supervisor; Fakulti Kejuruteraan Mekanikal (2011)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2011